Post-COVID multisystem inflammatory syndrome with myocardial involvement: Clinical case (Archives of Pediatrics of Uruguay, 2022)
In April 2020, during the peak of the COVID-19 pandemic caused by the emerging coronavirus SARS-CoV-2, 8 children reported cases of hyperinflammatory toxic shock with characteristics similar to Kawasaki disease and syndrome in the United Kingdom.The Royal College of Pediatrics and Child Health has called it pediatric Multisystem Inflammatory Syndrome (MIS) temporally associated with COVID-19.Currently, MIS-C is a rare disease, overlapping with other conditions, which requires a high clinical suspicion for its timely identification.Pediatric SARS-CoV-2-associated temporary multisystem inflammatory syndrome (TMIS-C) is a new clinical entity with a broad spectrum of presentation after exposure to the virus, immune-mediated with hyperinflammation and activation of a cytokine storm. It typically occurs between the 2nd to 4th week of evolution.Characteristically elevated markers of inflammation are described, such as ferritin, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), lactate dehydrogenase and D-dimer, associated with neutropenia, lymphopenia and anemia.The World Health Organization (WHO) defines it as: a case under 19 years of age with fever ≥ 3 days, elevated inflammatory markers, evidence of SARS-CoV-2 infection and no other microbial etiology; with involvement of at least 2 systems: dermatological (rash, non-exudative conjunctivitis, mucocutaneous inflammation), hemodynamic (hypotension, shock), cardiac (myocardial, pericardial, valvular, or coronary dysfunction), hematologic (coagulopathy), digestive (vomiting, diarrhea, abdominal pain)Considering the seriousness of this new entity, timely recognition and early referral for specialized care and timely treatment are key.
Keywords: Systemic inflammatory response syndrome; SARS-CoV-2; Cardiomyopathies; COVID-19